MARINE GEOMAGNETIC ANOMALY BELT AND ITS RELATIONSHIP TO THE REMNANT ARCS IN THE NORTHWESTERN JAVA SEA, INDONESIA - Dida Kusnida; Lukman Arifin (Marine Geological Institute of Indonesia, 2022)
The continuous marine geomagneticsurvey within a timeintervalof1-secondsampling and a precision of 0.1 nT was conducted in the northwestern Java Sea to identify and interpret the general trend of total marine magnetic anomalies and the possibility related to thegeological resourcepotential. These magnetic data were then processed according to the formula corrected and applied to marine magnetic data. The total marine magnetic anomalies of the northwestern Java Sea indicate a well-defined lateral trend belt of anomaly contours. Anomalies are divided into four delineation zones: Zones I, II, III, and IV. A preliminary analysis of these anomalies led to the interpretation, reflecting the residual of a slightly east-west trending geological body underneath.Examination of magnetic anomalies suggests Zone I and IV characterize a basinalarea, Zone II depicts a granitic belt, and Zone III describes a Cretaceousmagmatic arc system in the east that extends from Middle Java across the Java SeathroughSouthern Kalimantan. These magnetic anomalies seem to coincide with the free air gravity anomalies data derived from TOPEX satellite data.